An allelic series of starch-branching enzyme mutants in pea (Pisum sativum L.) reveals complex relationships with seed starch phenotypes. (15th July 2022) - Moreau, Carol; Warren, Frederick J.; Rayner, Tracey; Perez-Moral, Natalia; Lawson, David M.; Wang, Trevor L.; Domoney, Claire
Abstract: A set of mutant pea lines carrying induced mutations within the major seed-expressed starch-branching enzyme gene has been characterised at the molecular, chemical and agronomic levels. Eight of the induced mutations, three of which predicted a premature stop codon, were compared with the naturally occurring starch-branching enzyme mutation within the same genetic background. Starch, amylose and sugar measurements, coupled with analysis by ultra-high performance liquid chromatography-size exclusion chromatography of starches, identified a range of phenotypes which were grouped according to the nature of the mutation. Homology modelling of proteins supported the differences in phenotypes observed. Differences in field performance were evident for selected mutants, particularly in seed yield and mean seed weight traits for early compared with late spring sowings. The data show the potential of an allelic series of mutants at this locus for nutritional studies. Chemical compounds: starch, amylose, amylopectin, raffinose, stachyose, verbascose. Graphical abstract: Mutations impacting on the predicted structure of SBEI in pea are associated with variation in starch chain length distribution. Unlabelled Image